Computational Analysis of the Immune Infiltration Pattern and Candidate Diagnostic Biomarkers in Lumbar Disc Herniation - Li, Kai; Li, Shijue; Zhang, Haojie; Lei, Di; Lo, Wai Leung Ambrose; Ding, Minghui (Frontiers in Molecular Neuroscience, 2022)
Objectives: Lumbar disc herniation (LDH) is a musculoskeletal disease that contributes to low back pain, sciatica, and movement disorder. Existing studies suggested that the immune environment factors are the primary contributions to LDH. However, its etiology remains unknown. We sought to identify the potential diagnostic biomarkers and analyze the immune infiltration pattern in LDH. Methods: The whole-blood gene expression level profiles of GSE124272 and GSE150408 were downloaded from the Gene Expression Omnibus (GEO) database, including 25 LDH patients and 25 healthy volunteers. After merging the two microarray datasets, Differentially Expressed Genes (DEGs) were screened and functional correlation analysis was performed. The Least Absolute Shrinkage and Selection Operator (LASSO) logistic regression algorithm and support vector machine recursive feature elimination (SVM-RFE) were applied to identify diagnostic biomarkers by cross-validation method. Then, the GSE42611 dataset was used as a validation dataset to detect the expression level of these diagnostic biomarkers in the nucleus pulposus and evaluate their accuracy. Hub genes in the network were identified by the CIBERSORT tool and Weighted Gene Coexpression Network Analysis (WGCNA). Spearman correlation analysis between diagnostic markers and infiltrating immune cells was conducted to further illustrate the molecular immune mechanism of LDH. Results: The azurophil granule and the systemic lupus erythematosus pathway were significantly different between the healthy group and the LDH group after gene enrichment analysis. XLOC_l2_012836, lnc-FGD3-1, and SCARA5 were correlated with the immune cell infiltration in various degrees. In addition, five hub genes were identified that correlated with LDH, including AQP9, SIRPB2, SLC16A3, LILRB3, and HSPA6. Conclusions: XLOC_l2_012836, lnc-FGD3-1, and SCARA5 might be adopted for the early diagnosis of LDH. The five identified hub genes might have similar pathological mechanisms that contribute to the degeneration of the lumbar disc. The identified hub genes and immune infiltrating pattern extend the knowledge on the potential functioning mechanisms which offers guidance for the development of therapeutic targets of LDH.